Quantitative Structure-Activity Analysis of 1,3,5-Trisubstituted Pyrazoline Derivatives as Monoamine Oxidase Inhibitors - Mishra, Vikash; K. Kashaw, Sushil; Kumar, Ajay (Asian Journal of Chemistry, 2011)
Quantitative structure activity relationship (QSAR) study has been performed on twenty four derivatives of 1,3,5-trisubstituted pyrazolines for identifying important physicochemical properties responsible for their binding affinity towards monoamineoxidase enzyme. QSAR study was performed using various physicochemical (hydrophobic, electronic, steric, etc.) parameters as independent variables and monoamine oxidase inhibitory activity as dependent parameter. The 2D QSAR studies revealed that the activity is mainly influenced by hydrophobicity parameter, where the hydrophobicity (log P) contributes negatively and polorizability parameter (MR) contributes positively towards the biological activity. All derived models display satisfactory correlation coefficient (> 0.7).